Comparison of the efficacy of artemether-lumefantrine vs. artesunate plus sulfadoxine-pyrimethamine in children with uncomplicated falciparum malaria - Rachmawati Rachmawati; Novie H Rampengan; Suryadi N N Tatura; Tonny H Rampengan (Indonesian Pediatric Society, 2010)
Background World Health Organization (WHO) has recommendedthat countries with drug resistant malaria problem usecombination therapies, especially artemisinin-based combinationtherapy (ACT). However, there is limited information on theefficacy of ACT in North Sulawesi.Objective To compare the efficacy of artemether-lumefanttine andartesunate plus sulfadoxine-pyrimethamine (SP).Methods This was a randomized experimental study, conducted inProf. Dr. R. D. Kandou General Hospital, Manado from Januaryuntil July 2009. There were 42 patients aged less than 13 yearstreated with artemether-lumefanttine and artesunate plus SP. Bodytemperature, parasite and gametocyte count were recorded everyday until day 7 and follow-up reviews were done on day 14 and28.Results Fever clearance time showed a significant differencebetween artemether-lumefanttine group (median 27 hours) andartesunate plus SP group (median 18 hours), P<0.05). There wasno significant difference in parasite clearance time (P>0.05) andgame tocyte clearance time (P > 0. 05) . The 28 day cure rate were100% in the two groups. No side effect was found.Conclusion Both artemether-lumefanttine and artesunate plus SPcombination are effective and safe for the treatment of falciparummalaria in children.